Is the female sex associated with an increased risk for long-term cognitive decline after the first-ever lacunar stroke? Prospective study on small vessel disease cohort - Pavlovic, Aleksandra; Pekmezovic, Tatjana; Mijajlovic, Milija; Tomic, Gordana; Zidverc Trajkovic, Jasna (Frontiers in Neurology, 2023)
Background. Sex is a significant determinant of survival and functional outcome after stroke. Long-term cognitive outcome after acute lacunar stroke in the context of sex differences has been rarely reported. Methods. A cohort of small vessel disease (SVD) patients presenting with first-ever acute lacunar stroke and normal cognitive status has been evaluated 4 years after the qualifying event for the presence of cognitive impairment (CI) with a comprehensive neuropsy-chological battery. Differences in baseline clinical and neuroimaging characteristics were com-pared between sexes in relation to cognitive status. Results. A total of 124 female and 150 male patients were analyzed. No difference was detected between the groups regarding age (p=0.932) or frequency of common vascular risk factors (p>0.1 for all). At the baseline assessment, wom-en had more disability compared to men with a mean modified Rankin scale (mRS) score of 2.5 (1.5 in men, p<0.0001). Scores of white matter hyperintensities (WMH) of presumed vascular origin and a total number of lacunes of presumed vascular origin on brain MRI were higher in women compared to men (p<0.0001 for all). As many as 64.6% of patients had CI of any sever-ity on follow-up, women more frequently (77.4%) than men (54.0%; p<0.0001). Univariate lo-gistic regression analysis showed that female sex, higher NIHSS and mRS score, presence of depression and increasing WMH severity were associated with an increased risk for CI. Multi-variate regression analysis indicated that only depression (OR 1.74, 95%CI 1.25-2.44; p=0.001) and WMH severity (OR 1.10, 95%CI 1.03-1.17; p=0.004) were independently associated with the CI. Conclusion. At long-term follow-up, female lacunar stroke survivors compared to men more frequently had CI in the presence of more severe vascular brain lesions, but this associa-tion was dependent of occurrence of depression and severity of WMH, and could not be ex-plained by differences in common vascular risk factors.